Comparison of the point of care test (POCT), i-CHROMA™ human chorionic gonadotrophin (HCG), leutinzing hormone (LH) and follicle stimulating hormone (FSH) methods with the other laboratory methods in the Randox International Quality Assessment Scheme (RIQAS). Issue 4 (2017) - Bolodeoku, John; Bains, Suman; Pinkney, Stuart; Coker, Olu; Fakokunde, Abiodun
No abstract available